2020
DOI: 10.1017/9781108776585
|View full text |Cite
|
Sign up to set email alerts
|

Limits of Supranational Justice

Abstract: With its contextualized analysis of the European Court of Human Rights' (ECtHR) engagement in Turkey's Kurdish conflict since the early 1990s, Limits of Supranational Justice makes a much-needed contribution to scholarships on supranational courts and legal mobilization. Based on a socio-legal account of the efforts of Kurdish lawyers in mobilizing the ECtHR on behalf of abducted, executed, tortured and displaced civilians under emergency rule, and a doctrinal legal analysis of the ECtHR's jurisprudence in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Lawyers' role is perhaps even more important in international litigation as domestic actors may be ill-informed about the availability of legal remedies at the international level. Scholars of international legal mobilization have shown that activist-lawyers, often working at transnationally connected and wealthy NGOs, lead litigation campaigns and help build an international court's case law in a new issue area (Anagnostou, 2014;Cichowski, 2007Cichowski, , 2016Haddad, 2018;Hodson, 2014;Kurban, 2020;Pavone, 2022;Sundstrom, 2014;Van der Vet, 2018).…”
Section: Theorizing Legal Mobilization and Multiple Avenues At The In...mentioning
confidence: 99%
See 2 more Smart Citations
“…Lawyers' role is perhaps even more important in international litigation as domestic actors may be ill-informed about the availability of legal remedies at the international level. Scholars of international legal mobilization have shown that activist-lawyers, often working at transnationally connected and wealthy NGOs, lead litigation campaigns and help build an international court's case law in a new issue area (Anagnostou, 2014;Cichowski, 2007Cichowski, , 2016Haddad, 2018;Hodson, 2014;Kurban, 2020;Pavone, 2022;Sundstrom, 2014;Van der Vet, 2018).…”
Section: Theorizing Legal Mobilization and Multiple Avenues At The In...mentioning
confidence: 99%
“…Especially during periods of judicial activism, activists can help shape the kinds of precedents international institutions set by bringing in new rights claims before them. The persuasive arguments, facts, and evidence about on-the-ground violations summoned by legal experts provide a much-needed supply of data to judges building case law in a new issue area (Anagnostou, 2014;Cichowski, 2007Cichowski, , 2016Haddad, 2018;Hodson, 2014;Kurban, 2020;Pavone, 2022;Sundstrom, 2014;Van der Vet, 2018). This iterative process suggests that judicial responsiveness and legal mobilization are mutually constitutive of each other.…”
Section: Theorizing Legal Mobilization and Multiple Avenues At The In...mentioning
confidence: 99%
See 1 more Smart Citation
“…The new policy had the effect of erasing Kurdish identity. Turkish nationalism or “Turkification” metastasized in the provinces to convert Kurds to “good Turks” (McDowall 2003, 194–202) by the establishment of the People’s Houses (Kurban 2020, 89). Following that, the geographical term “Kurdistan” was expunged from the books (Van Bruinessen 1992, 282), a process which has continued to the present.…”
Section: The Partition Of Kurdistanmentioning
confidence: 99%
“…By examining how rights advocates navigate this space, we wish to go beyond successful cases, or what Helen Duffy (2018) has called the "champagne moment" in strategic litigation, which focuses on judgments alone and presumes a linear pathway from litigant to judgment to successful policy reform. Studies of international litigation have shown that rights advocates are active far before and after these judgments: they select strategic cases to forward to international courts, persuade judges of the soundness of the claims (sometimes after numerous unsuccessful attempts), engage in follow-up advocacy for the domestic implementation of final judgments, and often proliferate their best practices by training other activists (Duffy, 2018;Haddad, 2018;Kahraman, 2018;Kurban, 2020;Sundstrom, 2012;van der Vet, 2012). Our collection of articles in this symposium explores the following themes:…”
mentioning
confidence: 99%